PRELIMINARY ESTIMATION OF THERMAL CONDUCTIVITY IN BORNU-CHAD BASIN, NIGERIA - Dieokuma, Tamunosiki; Ming, Gu Han; Uko, Etim D. (European Scientific Journal, ESJ, 2013)
Thermal conductivity estimates are computed from four randomly selected and spaced petroleum wells in the Bornu-Chad basin, Nigeria, using a geometric mean model. Sonic and gamma-ray logs were digitized and used in the estimation of in situ conductivity. The area under study is composed of 4 major diachronous lithostratigraphic units of Chad, Fika, Gongila and Bima formations, which form the bulk of the basin’s sediments. Porosity, lithology, and depth of burial exert the most important control on the matrix thermal conductivity in the basin. There is a decrease of thermal conductivity with increasing shale fraction. The bulk conductivity also shows an increase with increasing sandstone fraction. Increase in porosity results in a decrease in bulk conductivity. Thermal conductivity values and variations for a given lithologic unit are reduced at increased porosity, such that thermal conductivity of the topmost continental Chad sandstone Formation vary between 2.055W/m°C and 2.854W/m°C with an average of 2.397W/m°C. Thermal conductivity for the underlying, marine shaly-sandstone Fika formation varies between 1.895W/m°C and 2.860W/m°C with an average of 2.432W/m°C. Furthermore, the thermal conductivity for the Gongila formation varies between 2.382W/m°C and 2.557W/m°C with an average of 2.470W/m°C, while Bima formation has thermal conductivity of 2.080 W/m°C and 3.580 W/m°C with an average of 2.879 W/m°C.